The Effects Of Corporate Governance On Firm Performance: Evidence From The Construction Sector - Wong, Choon Wai (2022)
Public listed companies play an important roles to stimulate and stabilized the economy of a country. Therefore, BURSA is playing an important role in monitoring the compliant of listed companies in Malaysia. History has proven the failure of corporate compliant, fraudulent and the like which has damaged multiply huge corporate, the economy and the society. Therefore, this research study will examines the effectives of corporate governance mechanism on seven independent variables namely CEO Duality, Board Structure (Board Size), Numbers of Independent Directors (Audit Committee), Numbers of Independent Directors (Remuneration Committee), Numbers of Independent Directors (Nomination Committee), Independent Directors on Board, Gender Diversity (Female Directors on Board) with Firm Size as the control variables on 44 public listed construction companies in Malaysia in terms of ROA, ROE and Tobin’s Q as dependent variables on Firm Performance. The data collected on 44-companies annual reports and Bloomberg in spreadsheet format will go through Eviews version 11 panel data regression analysis to determine the significant of each independent variables towards each dependent variables. Each hypotheses will be answered accordingly. Based on the study, there are not all independent variables are significant to firm performance. As such, it would be strongly suggests that more factors to be included in the research study which might possible have influence on the firm performance.